Gambaran Kadar Kalsium Pada Pasien Gagal Ginjal Kronik Penderita Anemia dan Non Anemia - Pramana, Gerry; Rahayu, Cahyawati; Kristianingsih, Yuli (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Chronic Kidney Failure (CKD) can be defined as a decrease in the Kidney Filtration Rate (GFR) for ≥ 3 months which can later cause fluids, electrolytes and waste to accumulate in the body and cause various complications. One high-risk complication that can worsen the manifestations is Anemia. When the kidneys are damaged, the production of erythropoietin (the hormone that regulates erythrocyte production) will decrease, where if erythrocyte production is reduced then anemia occurs. Under normal circumstances, phosphate and calcium are in balance with a reciprocal relationship (pathonomonics). When GFR decreases, the concentration of phosphate in the plasma will increase, which will later combine with calcium to form calcium phosphate, so that the calcium concentration will decrease (Hypocalcemia). The aim of this study was to determine the description of calcium levels in CKD patients with Anemia and non-Anemia at the Bio Medika Kedoya Clinical Laboratory. This research was carried out descriptively using 202 secondary data from CKD patients suffering from anemia and non anemia taken from January 2022 - December 2023. The results of the study showed that 140 patients (69.3%) experienced hypocalcemia with the result of hypocalcemia in CKD patients who also suffered from anemia. many, namely 102 patients (50.5%) with an average calcium level of 8.37 mg/dL. The prevalence of male CKD patients was higher at 121 patients (59.9%) compared to female patients at 81 patients (40.1%). And based on age group, the highest percentage was found in elderly aged ≥ 60 years) as many as 172 patients (85.1%). From this research it can be concluded that it is important to carry out laboratory examinations for CKD diseases such as GFR because new symptoms can be felt when the condition gets worse and it is important to check for complications that may occur such as anemia and hypocalcemia which will later cause osteomalacia, osteoporosis and ectopic calcification. Keywords: Anemia, Chronic Kidney Failure, Calcium